Pengaruh Keterlibatan Organisasi Mahasiswa terhadap Keaktifan Pembelajaran - Verina Rahma Widiasari; Arya Mangatur Manik; Shalina Niswa Ayyanus Saqi; Dwi Yuliani; Revin Sucipta Wijaya (Universitas Djuanda, 2026)
This study examines the influence of student organizational involvement on classroom learning activeness among first-year students of the Faculty of Social and Political Sciences at Universitas Tidar. The research is motivated by the common assumption that organizational activities may distract students from academic responsibilities, prompting the need for empirical evidence to assess whether such activities hinder or instead enhance classroom participation. Using a quantitative method with a causal design, the study selected 90 respondents through simple random sampling from a population of 674 students. Data were collected using a five-point Likert-scale questionnaire and analyzed through validity and reliability tests, normality testing, Spearman correlation, and simple linear regression. The findings reveal a positive and significant effect of organizational involvement on students’ learning activeness, challenging the notion that extracurricular engagement undermines academic focus. The novelty of this research lies in its emphasis on learning activeness as the core variable and its focus on first-year students who are undergoing both academic and social adaptation. These results highlight the role of student organizations as not merely extracurricular spaces but as contributors to the development of constructive learning attitudes, offering implications for policies on student development and organizational guidance.